2022
DOI: 10.1093/ofid/ofac492.1892
|View full text |Cite
|
Sign up to set email alerts
|

LB2302. Ceftobiprole Compared to Daptomycin With or Without Optional Aztreonam for the Treatment of Complicated Staphylococcus aureus (SAB): Results of a Phase 3, Randomized, Double-Blind Trial (ERADICATE)

Abstract: Background SAB is common, serious, and potentially lethal. Antibiotic options are limited, especially for MRSA. Ceftobiprole is an advanced-generation cephalosporin with bactericidal activity against Gram-positive (including MRSA) and Gram-negative pathogens, with efficacy and safety demonstrated in previous Phase 3 studies in acute bacterial skin infections and pneumonia. The present study evaluated ceftobiprole in patients with complicated SAB. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…According to the promising results of the recent ERADICATE RCT, which included 20 patients with S. aureus IE, a green/yellow colour was attributed to BPR for S. aureus, similar to the evidence available for BPR and DAP (Figure 1A) [39]. However, we believe that the use of BPR for the treatment of staphylococcal IE (alone or in combination with DAP) will increase over time.…”
Section: New Therapeutic Strategies: Considerations For Their Optimal...supporting
confidence: 66%
See 3 more Smart Citations
“…According to the promising results of the recent ERADICATE RCT, which included 20 patients with S. aureus IE, a green/yellow colour was attributed to BPR for S. aureus, similar to the evidence available for BPR and DAP (Figure 1A) [39]. However, we believe that the use of BPR for the treatment of staphylococcal IE (alone or in combination with DAP) will increase over time.…”
Section: New Therapeutic Strategies: Considerations For Their Optimal...supporting
confidence: 66%
“…Daptomycin (DAP) was administered at a dosage ranging from 6 mg/Kg to 10 mg/Kg q24h, while BPR was given at a dosage of 500 mg q6h from Day 1 to Day 8 and 500 mg q8h from Day 9 onwards, with dose adjustments according to renal function. The study showed the non-inferiority of BPR compared to DAP in terms of mortality rates, microbiological eradication, and the occurrence of new complications associated with bacteraemia (overall clinical success: 69.8% in BPR-regimen vs 68.7% in DAP-regimen) [39,41].…”
Section: Clinical Evidence In Infective Endocarditismentioning
confidence: 95%
See 2 more Smart Citations
“…8-hourly useful for pathogens with higher MICs or difficult to penetrate sites of infection [52]. In a phase 3, randomized, double blind trial, ceftobiprole was noninferior to daptomycin (with or without aztreonam) for complicated SAB [53]. Daptomycin was dosed as 6 mg/kg (up to 10 mg/kg) i.v.…”
Section: Cephalosporinsmentioning
confidence: 99%